Implementation Of The Project Learning (PJBL) Model In Improving Learning Outcomes Of Integrated Islamic Primary School Students - Usamah; Nurul Huda SA (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem : This research aims to determine the escalation of learning outcomes on the theme of economic business for class 5A students (Integrated Islamic School) SDIT Nurul Fikri Banjarmasin with apply model PjBL (Project Based Learning) Purpose : This Study use 2 Cycle, on every the cycle arranged on compile plan, carry out, observe and reflect. Design/methods/approach: The subjects in this research are Class 5A students at SDIT Nurul Fikri Banjarmasin totaling 27 students. Researcher using techniques analysis descriptive qualitative and descriptive quantitative. Analysis results data is collected through observation and test. Findings : Learning Thematic Payload Social Sciences on material business economy through learning model PjBL (Project Based Learning) can improving the learning outcomes of class 5A students at SDIT Nurul Fikri Banjarmasin. This is supported by the pre-cycle test results which are average is 55.3. After implementation Cycle I average value acquisition student of 72.7 and a classical completeness score of 37.03% or 10 people from 27 student Already finished, whereas Which Still Not yet complete 17 person. After That on cycle II obtained mark average acquisition student namely 86.03 and classical completeness of 88.88% or 24 of 27 person Already complete. Viewed from cycle I And II application model PjBl (Project Based Learning) on lesson Thematic load Social Sciences results occur study student increase very well. Research implications/limitations: The research has several limitations, especially in the selection of research subjects and analysis. Originality/value : It is hoped that the research results will become a simple guideline for subsequent research.